Chart exhibiting the discoveries of the second American Grinnell Expedition in search of Sir John Franklin unrevised from the original material and projected on the spot / E.K. Kane Lith. of J. Bien - Kane, Elisha Kent, 1820-1857; Grinnell, Henry, 1799-1874. (N.Y. : Lith. of J. Bien, 1855)
Deposited November 15th, 1855 "Deposited Nov. 15th, 1855. - E.K.K." Relief shown by hachures. Grayscale; 1:600,000